2015
DOI: 10.1037/pspi0000028
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive adaptations to stressful environments: When childhood adversity enhances adult executive function.

Abstract: Can growing up in a stressful childhood environment enhance certain cognitive functions? Drawing participants from higher-income and lower-income backgrounds, we tested how adults who grew up in harsh or unpredictable environments fared on 2 types of executive function tasks: inhibition and shifting. People who experienced unpredictable childhoods performed worse at inhibition (overriding dominant responses), but performed better at shifting (efficiently switching between different tasks). This finding is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
329
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(377 citation statements)
references
References 87 publications
(139 reference statements)
19
329
4
1
Order By: Relevance
“…For example, Blackwell, Chatham, Wiseheart, and Munakata (2014) found that children who were better at switching in a card-sorting task were worse at response inhibition. Similarly, Mittal, Griskevicius, Simpson, Sung, and Young (2015) found that adults who had grown up in stressful environments showed worse response inhibition but better task switching in uncertain contexts, compared to adults raised in less stressful environments.…”
Section: Unity/diversity Framework For Individual Differences In Efsmentioning
confidence: 90%
“…For example, Blackwell, Chatham, Wiseheart, and Munakata (2014) found that children who were better at switching in a card-sorting task were worse at response inhibition. Similarly, Mittal, Griskevicius, Simpson, Sung, and Young (2015) found that adults who had grown up in stressful environments showed worse response inhibition but better task switching in uncertain contexts, compared to adults raised in less stressful environments.…”
Section: Unity/diversity Framework For Individual Differences In Efsmentioning
confidence: 90%
“…[46]) and how these skills can be usefully employed in relevant contexts. An example is heightened attention-shifting ability among individuals who grow up in harsh, unpredictable home environments and then are exposed to current states of economic decline and uncertainty [47 ‱‱ ]. Heightened attention-shifting ability may facilitate vigilance in a world where threats come without warning.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Thus, within harsh rearing contexts characterized by limited caregiver investment and resources, individuals are likely to shift toward here‐and‐now survival and early reproduction strategies (Belsky, Schlomer, & Ellis, ), defined as a ‘fast’ life history approach. Behavioral studies have documented associations between environmental harshness and increased risk‐taking behavior, including aggression (e.g., Doom, VanZomeren‐Dohm, & Simpson, ), lower inhibitory control (e.g., Mittal, Griskevicius, Simpson, Sung, & Young, ), and greater orientation toward immediate rewards (Humphreys et al., ; Sturge‐Apple et al., ). In the present study we examined whether early exposure to harsh environments (e.g., low maternal investment and economic resources) positively predicts enhanced problem‐solving for rewarding stimuli, consistent with a ‘fast’ life history strategy.…”
Section: Introductionmentioning
confidence: 99%